Glenohumeral synovitis score predicts early shoulder stiffness following arthroscopic rotator cuff repair - Tan, Zhen (J Orthop, 2020)
BACKGROUND: This study was conducted to determine if there is an association between an intraoperative glenohumeral synovitis score (GHSS) and postoperative shoulder stiffness in patients undergoing arthroscopic rotator cuff repair (ARCR). METHODS: Intraoperative GHSS was collected retrospectively from standardized arthroscopic images on consecutive patients undergoing primary ARCR. Range of motion was collected preoperatively and postoperatively at 3 and 6 months. RESULTS: 290 consecutive patients underwent primary ARCR. At three-months follow-up, 32 (11.0%) patients had glenohumeral stiffness. Patients with stiffness had significantly higher mean GHSS. CONCLUSION: Higher intraoperative GHSS was associated with early postoperative shoulder stiffness at three-months after ARCR.